The Role of the Police in Eradication of Motor Vehicle Theft Cases at Jambi Police Office - Dwitama, Muhammad Yoga; Arpangi, ‎ (KnE Social Sciences, 2025)
This study examines the role of the police in eradicating motor vehicle theft cases at the Jambi Police Department. This research method uses a sociological juridical approach, examining social phenomena based on data and facts obtained from direct observation, interviews, or experiments in the field. The results indicate that the Jambi Police Department has a strategic role in efforts to eradicate motor vehicle theft not only as a law enforcer but also as a protector and servant of the community. This role is realized through patrol activities, investigations, enforcement, and counseling to residents to increase awareness. Internal factors such as minimal operational facilities and external obstacles such as low public awareness and high unemployment are the main obstacles. The solutions include increasing synergy between agencies, improving service quality, and fostering active community involvement in maintaining security. The strategies implemented include preventive, repressive, and preemptive approaches to reducing crime rates. To overcome obstacles to implementation, the Jambi Police Department strengthens human resource capacity, establishes crosssector cooperation, and utilizes information technology in reporting and monitoring cases.